Diesel, Conventional Gas, Jet Fuel, and Natural Gas Equity and Commodity Project Risk across the Oil and Gas Industry - Scott Alan Carson (Center for Economic Studies and ifo Institute (CESifo), 2022)
Oil and gas company returns are compared between upstream, midstream, and down-stream sectors from 2000 through 2020. Crude oil, natural gas, and distillate returns reflect project risk, infrastructure, and conditions within the industry. Equity, commodity, and distillate markets positively price returns, and equity market risk and returns are higher than for commodity markets. Refining & marketing and equipment & service firms have the greatest equity market risk, while equipment & service and exploration & production firms have the greatest commodity market risk. Refining & marketing firm returns did not systematically vary with commodity market risk. Producer returns are positively related to crude distillates, and across the oil and gas industry, diesel has the greatest risk and distillate return. Equity, commodity, and distillate returns are collectively significant in individual risk and returns.
Keywords: G12; L71; L72; Q40; Q41; 330; oil and gas asset pricing models; book to market; size; oil and gas sector